'Socialism is not just Built for a Hundred Years': Renewable Energy and Planetary Thought in the Early Soviet Union (1917–1945). (November 2022) - Russ, Daniela
Abstract : The humanities recently rediscovered the category of the 'planetary' for a social theory of the Anthropocene critical of the human remaking of the planet. This article brings together Dipesh Chakrabarty's work with Russian planetary and geopolitical thought. Focusing on Vladimir Vernadsky's and Boris Veinberg's research around the Commission for the Study of Natural Productive Forces, it argues that knowledge on planetary interconnections informed the territorial and industrial expansion of the Russian Empire and the Soviet Union. According to planetary scientists, humanity's peculiarity as a species and planetary reach hinged on its control of energy. As 'cosmic technologies', wind and solar power could expand the biosphere and make the territory's fringes habitable. Thus, insight into the vast scales of the universe did not dwarf but augment humanity – and particularly scientists. The article concludes that the planetary should be understood as an extension of global politics rather than a divergence from it.